Graphene modified anatase/titanate nanosheets with enhanced photocatalytic activity for efficient degradation of sulfamethazine under simulated solar light - Xiaona Liu; Ji, Haodong; Si Li; Liu, Wen (Chemosphere, 2019)
Graphene modified anatase/titanate nanosheets (G/A/TNS) synthesized through hydrothermal treatment were used for solar-light-driven photocatalytic degradation of a typical pharmaceutically active compound, sulfamethazine (SMT). The optimal material was synthesized with 0.5 wt% of graphene loading (G/A/TNS-0.5), which could efficiently degrade 96.1% of SMT at 4 h. G/A/TNS-0.5 showed enhanced photocatalytic activity compared with the neat anatase and unmodified anatase/titanate nanosheets (A/TNS). UV–vis diffuse reflection spectra indicated that G/A/TNS-0.5 had a lower energy band gap (Eg) of 2.8 eV than A/TNS (3.1 eV). The grafted graphene acted as an electron transfer mediator after photoexcitation, resulting in inhibition on rapid recombination of electron-hole pairs. More importantly, architecture of graphene and titanate nanosheets both with two-dimensional structures greatly facilitated the photoexcited electron transfer. •OH and 1O2 were the primary reactive oxygen species (ROS) to SMT degradation. Fukui index (f -) derived from density functional theory (DFT) calculation predicted the active sites on SMT molecule, and then SMT degradation pathway was proposed by means of intermediates identification and theoretical calculation. Furthermore, G/A/TNS-0.5 could be well reused and 90.5% of SMT was also degraded after five runs. The developed new photocatalysts show great potential for degradation of emerging organic contaminants through photocatalysis under solar light.
Keywords: DFT calculation; Graphene; Pharmaceuticals; Photocatalysis; Titanium nanomaterials